Knowledge, Attitude and Practices Towards Dengue Fever Among Slum Dwellers: A Case Study in Dhaka City, Bangladesh - Rahman, Md. Mostafizur; Tanni, Kamrun Nahar; Roy, Tuly; Islam, Md. Rakibul; Al Raji Rumi, Md. Alim; Sadman Sakib, Mohammed; Abdul Quader, Masrur; Bhuiyan, Nafee-Ul-Islam; Shobuj, Ifta Alam; Sayara Rahman, Afra; Haque, Md. Iftekharul; Faruk, Fariha; et al. (International Journal of Public Health, 2023)
Objectives: This study intends to evaluate Dhaka city slum dwellers’ responses to Dengue fever (DF). Methods: Face-to-face interviews were performed to obtain data. Python with RStudio was used for data management and analysis. The regression models were applied when applicable. Results: 745 individuals participated in a KAP survey that was pre-tested. More than 75% felt that COVID-19 might negatively affect DF surveillance activities. In terms of DF control knowledge and practices, they were lacking. The increased knowledge of individuals might lead to changes in behavior about DF. Education and types of media for DF information were shown to promote DF prevention practices. Conclusions: Overall, Dhaka's slums require dengue monitoring initiatives with sufficient campaigns for behavioral change. This finding might be incorporated into other DF-affected areas' dengue outbreak prevention plans.